Assessing Diet of the Rufous-Winged Philentoma (Philentoma pyrhoptera) in Lowland Tropical Forest using Next-Generation Sequencing - Mansor, Mohammad Saiful; Nor, Shukor Md; Ramli, Rosli (Penerbit Universiti Kebangsaan Malaysia, 2018)
Dietary study provides understanding in predator-prey relationships, yet diet of tropical forest birds is poorly understood. In this study, a non-invasive method, next-generation sequencing (Illumina MiSeq platform) was used to identify prey in the faecal samples of the Rufous-winged Philentoma (Philentoma pyrhoptera). Dietary samples were collected in lowland tropical forest of central Peninsular Malaysia. A general invertebrate primer pair was used for the first time to assess diet of tropical birds. The USEARCH was used to cluster the COI mtDNA sequences into Operational Taxonomic Unit (OTU). OTU sequences were aligned and queried through the GenBank or Biodiversity of Life Database (BOLD). We identified 26 distinct arthropod taxa from 31 OTUs. Of all OTUs, there was three that could be identified up to species level, 20 to genus level, three to family level and five could not assigned to any taxa (theBLAST hits were poor). All sequences were identified to class Insecta belonging to 18 families from four orders, where Lepidoptera representing major insect order consumed by study bird species. This non-invasive molecular approach provides a practical and rapid technique to understand of how energy flows across ecosystems. This technique could be very useful to screen for possible particular pest insects consumed by insectivores (e.g. birds and bats) in crop plantation. A comprehensive arthropod studies and local reference sequences need to be added to the database to improve the proportion of sequences that can be identified.